Über die Hyperflächen des metrischen Raumes von Hyperebenenelementen - Medviedevaitė, I. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Х. Медведевайте. О гиперповерхности метрического пространства гиперплоских элементовI. Medviedevaitė. Apie metrinės hiperplokštuminių elementų erdvės hiperpaviršius